The Impact of Social Media on Family Relationships as Perceived by Children (Abhat Journal, 2023)
The research aims to identify the level of family members' use of social communication means, and to identify the impact of social communication on family relations as perceived by children, and the impact of social communication on the erosion of some values within the family as perceived by children. The research sample consisted of (170) students, and to achieve For these objectives, the researcher used the descriptive approach, due to its suitability and the nature of the research, and the results revealed the following: Most of the sample members spend three hours or more on social media, and the results found an impact of social media on family relationships. Family relations, and there is a weak degree of influence of social media on the erosion of some values within the family, and most of the respondents use the Facebook network
Keywords: effect; means of communication; family; relationships